Rola deontologii weterynaryjnej w ochronie zwierząt i ich praw - Helios, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Due to the fact that today the profession of a veterinary surgeon is quite popular, the ethics of the profession is becoming increasingly important. Professional ethics in veterinary medicine is similar to the ethics of the medical profession of medical sciences. Both the veterinarian and a doctor of medical sciences are committed to help the needy. If a veterinarian meets an animal in need, whose moral status and the legal situation is not entirely fixed, it is dependent on a man, and the veterinary deontology can help in securing good animal.
Keywords: lekarz weterynarii; etyka